2013
DOI: 10.2215/cjn.01540213
|View full text |Cite
|
Sign up to set email alerts
|

Use of Peritoneal Dialysis in AKI

Abstract: SummaryBackground and objectives The role of peritoneal dialysis in the management of AKI is not well defined, although it remains frequently used, especially in low-resource settings. A systematic review was performed to describe outcomes in AKI treated with peritoneal dialysis and compare peritoneal dialysis with extracorporeal blood purification, such as continuous or intermittent hemodialysis.Design, setting, participants, & measurements MEDLINE, CINAHL, and Central Register of Controlled Trials were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 37 publications
(119 reference statements)
0
121
0
9
Order By: Relevance
“…Peritoneal dialysis, however, continued to be used in low resource settings even though its use was, to some extent, called into question by the randomized trial from Vietnam published in the New England Journal of Medicine in 2002 (2). This study suggested a higher mortality rate for patients with AKI treated with PD compared to hemofiltration; the obvious problems with this study have been discussed previously (3).…”
mentioning
confidence: 85%
“…Peritoneal dialysis, however, continued to be used in low resource settings even though its use was, to some extent, called into question by the randomized trial from Vietnam published in the New England Journal of Medicine in 2002 (2). This study suggested a higher mortality rate for patients with AKI treated with PD compared to hemofiltration; the obvious problems with this study have been discussed previously (3).…”
mentioning
confidence: 85%
“…If one extrapolates from extracorporeal studies the minimum optimal dose would be a weekly Kt/V of 2.1 (16). Until these 2 doses have been compared head to head, the former should be considered optimal but the latter is the minimum standard.…”
Section: Rationalementioning
confidence: 99%
“…A systematic review published by Chionh et al 53 concluded that there is currently no evidence to suggest significant differences in mortality between PD and extracorporeal blood purification in AKI and there is a need for good-quality evidence in this important area.…”
Section: Pd Outcomes In Akimentioning
confidence: 99%